Pengembangan Sistem Informasi untuk Manajemen Alat Topografi di Perusahaan Konstruksi - Fahmi, Rades (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
This research focuses on the development and implementation of an Information System for managing topographic instruments within construction companies. The proposed system aims to improve the efficiency and accuracy of equipment tracking, maintenance scheduling, and usage monitoring. By integrating features such as real-time location tracking, automated maintenance reminders, and comprehensive usage logs, the system provides a robust solution for managing topographic instruments. The system also includes functionalities for inventory management, ensuring that all equipment is accounted for and readily available when needed. The study outlines the design and development process of the system, including the selection of appropriate technologies, system architecture, and user interface design. Furthermore, the research highlights the benefits of the system in terms of reducing equipment downtime, extending the lifespan of instruments, and enhancing overall project management efficiency. The implementation of this system is expected to lead to significant cost savings and improved operational efficiency for construction companies. Challenges encountered during the development and deployment phases are discussed, along with the strategies adopted to overcome them.